Optimizing care transitions: the role of the community pharmacist - Melody KT; McCartney E; Sen S; Duenas G (Dove Medical Press, 2016)
Karleen T Melody, Elizabeth McCartney, Sanchita Sen, Gladys Duenas Department of Pharmacy Practice, Philadelphia College of Pharmacy, University of the Sciences, Philadelphia, PA, USA Abstract: Transitions of care (TOC) refer to the movement of patients across institutions, among providers, between different levels of care, and to and from home. Medication errors that occur during TOC have the potential to result in medical complications that are serious for the patient and costly to the health care system. Positive outcomes have been demonstrated when pharmacists are involved in providing TOC services, including reducing preventable adverse drug reactions, medication-related problems, and rehospitalizations, as well as improving the discharge process. This review explores TOC models involving community pharmacy practice, the current impact of pharmacist interventions in TOC, and patient satisfaction with TOC services provided by community pharmacists. Common barriers and potential solutions to TOC services provided in the community pharmacy, such as patient identification, information gathering, standardization of services, administrative support, reimbursement, and time restraints, are also discussed. Keywords: transitions of care, care transitions, post-discharge, community pharmacy, community pharmacist, community pharmacy services